Regional Funds of Scientific and Innovation Activity Support: Institutional Aspect - T. N. Topoleva (Вестник Российского экономического университета имени Г. В. Плеханова, 2021)
Shaping innovation economy in Russia stipulates passing-over from traditional partial models to system-integrated models of development accompanied by building institutional vector of succession of federal and regional institutions. A special role in processes of interaction between state, business and science is entrusted to institutions of development, which are to foster knowledge generation and successful practices of innovatization. The article studies specific features of scientific and innovation activity support funds, which help realize measures aimed at stimulating and raising efficiency of the scientific and innovation sector on the regional level. State support of institutions of development and science was analyzed and experience of such funds in the Krasnoyarsk area, Tatarstan, Perm area, Smolensk region was investigated as they demonstrate positive dynamics and adequacy in principle lines of functioning. Problems and drawbacks of these funds' work were systematized by 4 large groups: institutional and legal, finance and economic, organizational and managerial and social ones. On the basis of this analysis measures aimed at improving the organizational efficiency of funds and upgrading the regional innovation environment were identified. A conclusion was drawn about the necessity to intensify state and non-state support of fundamental and applied research, to stimulate setting-up of collaborative partnerships in order to raise scientific, technological and innovation competences in regions in view of solving strategic tasks of development.